Investigation of estrogenic activity in groundwater of Sao Paulo State - Quináglia, Gilson Alves (2017)
The endocrine disruptors are chemicals able to interfere with the action of hormones. They may be natural (estradiol, estriol, estrone) or synthetic hormones (ethinylestradiol, used for contraception), plasticizers such as bisphenol A, pesticides like DDT, among others. The high water demand in Sao Paulo State has led to an increase in groundwater exploitation, resulting in greater groundwater draw downs. Consequently, the input of surface water contaminated with endocrine disrupting compounds in groundwater will increase, especially in areas where high capacity wells are located near surface waters. These compounds can also reach the groundwater through leaching of septic system effluents or damaged sewage networks. In order to investigate the estrogenic activity in groundwaters of Sao Paulo State, CETESB used the BLYES bioassay (Bioluminescent Yeast Estrogen Screen) from 2011 to 2015. Out of 78 sampling sites in the monitoring program, 6 showed estrogenic activity higher than the quantification limit of the method, however, the values were below the trigger value 3.8 ng E2 eq L-1. These data indicate that the long-term consumption of groundwater poses no risk to human health. The results indicates that the groundwater of Sao Paulo State is still protected from the occurrence of estrogenic activity.